Determinan yang Berhubungan dengan Pemberian MP-ASI Dini pada Bayi Usia 0-6 Bulan - Oktova, Rafika (Jurnal Kesehatan, 2017)
SDKI (2012) said the distribution of MP-ASI early age in Indonesia: 0-1 months of 49,3%, at the age 2-3 month of 51%, and age 4-5 months of 73%. If complementary feeding given at the age of under six months, digestive system of infants have not having enzymes to digest food, digestion and kidney worked havier, can lead cough, diarrhea, colic, and allergic.The lowest percentage of the scope breastfeeding exclusive was at Puskesmas Rumbai Pesisir, about 37,27 %. This study was to know factors that deals with the provision of premature complementary feeding on children aged 6-0 months in the work area of Puskesmas Rumbai Pesisir Pekanbaru. This study was analytic design cross sectional. Population were all the mother who have a baby aged 6-0 months, total population were 1135 people, and 92 as total sample. Data were analyzed by test chi-square (α<0,05). Results were obtained the majority of respondents knowledgeable good 67 people (72,8%), educated low as many as 68 people (73,9%), does not work as many as 69 people (75%) and family income high 53 people (57,6%). Statistical tests chi-square revealed that there were relation between knowledge and education with the premature complementary feeding. And there was no related between work and family income with give premature complementary feeding. Expected health workers can cooperate with healthcare and community figures in providing information or tutoring directed regarding the provision of complementary feeding time.